AgPt bimetallic coated Ag nano material based on rGO negative charge regulation and control

By reducing AG nanomaterials covered by AGPT dual -metal over load on graphene, it solves the problem of poor stability and catalyst poisoning in complex environments, and achieves high -sensitivity and wide linear electrochemical detection effects.

CN119346858APending Publication Date: 2025-01-24NINGDE NORMAL UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411451005.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art has problems such as poor stability and catalyst poisoning in electrochemical detection of gallic acid in complex environments, and traditional detection methods are complex, expensive and have high operating technology requirements, which limits the application of rapid on-site detection.

Method used

Design an AG nanim material based on AGPT dual -metal -covered AGPT dual -metal -covered by restore oxygen oxygenne (RGO), which prepares the catalyst through the method of hydrophilic response and electrochemical modification electrodes, which improves the catalytic performance and stability.

Benefits of technology

The catalyst has excellent catalytic performance for gallic acid, high sensitivity, and wide linear range. It is suitable for electrochemical detection of gallic acid, effectively solves the problem of detection interference in complex environments, and provides a new solution to the poisoning and activity degradation of platinum metal catalysts. ideas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346858A_ABST
    Figure CN119346858A_ABST
Patent Text Reader

Abstract

The invention provides an AgPt bimetallic coated Ag nano-material based on rGO negative charge regulation and control, and a preparation method of the Ag nano-material comprises the following steps: adding a silver acetate solution into a graphene oxide aqueous solution, sequentially adding distilled water, ethylene glycol, methyl pyrrolidone and trisodium citrate, uniformly stirring, and carrying out a hydrothermal reaction; cooling, centrifuging, cleaning with a mixed solution of water and ethanol, centrifuging again, and repeatedly cleaning and centrifuging for multiple times to obtain a reduced graphene oxide loaded silver nano catalyst rGO / Ag; the preparation method comprises the following steps: dispersing rGO / Ag in an ethanol solution, adding potassium chloroplatinate, carrying out a stirring reaction, carrying out centrifugation, carrying out washing with a mixed solution of water and ethanol, carrying out centrifugation again, and carrying out repeated washing and centrifugation for many times so as to obtain a reduced graphene oxide loaded platinum-silver metal coated silver nano-catalyst rGO / Ag (at) AgPt; wherein the molar ratio of Ag to Pt is (10: 1)-(6: 1). The catalyst has excellent catalytic performance on gallic acid, and is high in sensitivity, wide in linear range and suitable for electrochemical detection of gallic acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an AgPt bimetal-coated Ag nanomaterial based on rGO negative charge regulation, belonging to the technical field of electrochemical materials. Background Art

[0002] Gallic acid (GA) is a natural organic acid found in plants such as tea, acorns, and gallnuts. It not only gives plants a unique flavor, but also brings multiple biological activities such as antioxidant, anti-inflammatory, and anti-tumor. However, excessive intake may be toxic to the human body. Therefore, the development of a rapid, accurate, and sensitive detection method is crucial to ensure food safety. Traditional methods of detecting gallic acid, such as high-performance liquid chromatography, liquid chromatography-mass spectrometry, and ultraviolet spectrophotometry, have excellent accuracy and sensitivity, but they are often plagued by complex sample pretreatment, expensive instruments and equipment, and high operating technical requirements. These factors greatly limit their application in on-site rapid detection. Therefore, exploring a simple, fast, and low-cost new method for detecting gallic acid is of great practical significance.

[0003] As an emerging analytical technology, electrochemical detection methods provide new possibilities for rapid quantitative analysis of gallic acid with their advantages of high sensitivity, rapid response, simple operation and instrument miniaturization. Many scholars have successfully detected gallic acid in food using various new electrochemical sensors. In particular, graphene-loaded precious metals, a new type of nanocomposite material, provides a new idea for improving the sensitivity and selectivity of electrochemical detection of gallic acid with its excellent electrocatalytic performance. However, in practical applications, in various complex test systems, the catalytic oxidation of various small molecules, including gallic acid in food, on the electrode surface always has practical problems such as poor stability and catalyst poisoning.

[0004] Graphene carriers have a variety of characteristic structures such as rich topological morphology and surface site defects. Their electronic structure is flexible and easy to control, which can provide a strong guarantee for the electronic structure control and performance optimization of graphene-based catalysts. Existing research has also found that two-dimensional graphene with carbon defects coupled with other metals exhibits excellent electrocatalytic performance. Among them, in the actual application of catalytic reactions of graphene-based composite materials loaded with precious metals, its promoting effect on catalytic reactions has been clearly demonstrated. Therefore, based on the diverse morphological characteristic structures of graphene, it is hoped that interface-enhanced precious metal catalysts can be designed to enable electrons to be transferred or activated in a more controllable, simple, and clear way to obtain better electrochemical catalytic performance.

[0005] Platinum-silver bimetallic catalysts have been widely used in many catalytic reactions due to their excellent catalytic performance and good anti-poisoning ability. Combining graphene with platinum-silver bimetallic can improve the activity of the catalyst, which shows high activity and good anti-poisoning ability in electrocatalytic reactions such as oxygen reduction reaction, hydrogen oxidation reaction, and methanol oxidation reaction. The reason can be attributed to the fact that the surface properties and electronic structure of graphene help to disperse metal particles and reduce the agglomeration and poisoning of catalysts during the reaction; it not only provides a large specific surface area, but also promotes electron transfer between platinum and silver metals, thereby enhancing the activity of the catalyst. In addition, due to the stability of graphene and the strong interaction between metal particles and graphene, the shedding and corrosion of metal particles are effectively inhibited, making it show good stability in long-term reactions.

[0006] Therefore, the design and development of graphene-supported platinum-silver bimetallic catalysts with excellent performance is not only promising to solve the catalytic oxidation of the target molecule gallic acid under complex environmental conditions, but also promising to provide an effective approach to solve the problems of metal catalyst poisoning and activity degradation, and has good application prospects in the fields of analysis and testing, environment, energy, etc. However, no ideal graphene-supported platinum-silver bimetallic catalyst has been reported in the prior art. Summary of the invention

[0007] The present invention provides an AgPt bimetallic-coated Ag nanomaterial based on rGO negative charge regulation, which can effectively solve the above problems.

[0008] The present invention is achieved in that:

[0009] A AgPt bimetallic-coated Ag nanomaterial based on rGO negative charge regulation, the preparation method of which comprises: adding a silver acetate solution to a graphene oxide aqueous solution, adding distilled water, ethylene glycol, methyl pyrrolidone and trisodium citrate in sequence, stirring evenly and then performing a hydrothermal reaction; cooling and then centrifuging, washing with a water and ethanol mixture and then centrifuging again, and repeatedly washing and centrifuging for multiple times to obtain a silver nanocatalyst rGO / Ag supported by reduced graphene oxide; dispersing rGO / Ag in an ethanol solution, adding potassium chloroplatinate, stirring for reaction and then centrifuging, washing with a water and ethanol mixture and then centrifuging again, and repeatedly washing and centrifuging for multiple times to obtain a platinum-silver metal-coated silver nanocatalyst rGO / Ag@AgPt supported by reduced graphene oxide; wherein the molar ratio of Ag:Pt is 10:1-6:1, respectively.

[0010] In some embodiments, the particle size of the rGO / Ag@AgPt is 40-50 nm.

[0011] A method for preparing Ag nanomaterials coated with AgPt bimetallic materials based on rGO negative charge regulation comprises the following steps:

[0012] S1, adding silver acetate solution to graphene oxide aqueous solution, and then adding distilled water, ethylene glycol, methyl pyrrolidone, and trisodium citrate in sequence, stirring evenly and then performing hydrothermal reaction; cooling and centrifuging, washing with a mixture of water and ethanol and then centrifuging again, and repeatedly washing and centrifuging multiple times to obtain a silver nanocatalyst rGO / Ag supported on reduced graphene oxide;

[0013] S2, dispersing rGO / Ag in an ethanol solution, adding potassium chloroplatinate, stirring the reaction and then centrifuging, washing with a mixture of water and ethanol and then centrifuging again, after repeated washing and centrifugation, obtaining a platinum-silver metal-coated silver nanocatalyst rGO / Ag@AgPt supported by reduced graphene oxide.

[0014] In some embodiments, the concentration of the silver acetate solution is 45-50 mmol / L; the graphene oxide aqueous solution is 1.8-2.2 mg / mL; and the potassium chloroplatinate is 8.0-8.4 mmol / L.

[0015] In some embodiments, the ratio of the silver acetate solution, graphene oxide aqueous solution, distilled water, ethylene glycol, methyl pyrrolidone, and trisodium citrate is 1.5-1.8 mL: 22-28 mL: 4-6 mL: 110-130 mL: 16-20 mL: 700-730 mg.

[0016] In some embodiments, in step S1, the temperature of the hydrothermal reaction is 110-130° C., and the time is 2.5-3.5 hours.

[0017] In some embodiments, in step S2, the stirring reaction time is 7-9 hours.

[0018] A method for preparing a modified electrode of AgPt bimetallic coated Ag nanomaterial based on rGO negative charge regulation, characterized in that it comprises the following steps:

[0019] (1) A glassy carbon electrode with a diameter of 5 mm was polished on a polishing pad with alumina slurries with particle sizes of 3, 1, 0.3 and 0.05 μm, respectively, rinsed with distilled water, ultrasonically cleaned in anhydrous ethanol and distilled water, and then dried for use; 2 mg of the above-mentioned reduced graphene oxide-supported platinum-silver metal-coated silver nanocatalyst rGO / Ag@AgPt powder and 10 μl of 5% Nafion ethanol solution were dispersed in 0.5 ml of ethanol and ultrasonicated for 30 min to form a uniform mixed suspension;

[0020] (2) 13 μl of the mixed suspension was added dropwise onto the surface of the cleaned glassy carbon electrode, and after drying at room temperature, 13 μl of the mixed suspension was added dropwise onto the surface of the glassy carbon electrode again, and after drying at room temperature, the electrode was immersed in a solution containing 5 mM sodium hypochlorite and 10% phosphoric acid for 24 h to reduce the graphene oxide to reduced graphene oxide, and to fully dope the graphene carrier and the Nafion membrane layer with phosphoric acid molecules;

[0021] (3) The prepared modified electrode was pretreated by performing cyclic voltammetry (CV) scanning for 0.5 h in a 5% phosphoric acid solution at a potential range of -0.3 V–0.9 V (vs. SCE); the pretreated modified electrode was immersed in a solution containing 5 mM sodium hypochlorite and 10% phosphoric acid for standby use.

[0022] A modified electrode of AgPt bimetallic coated Ag nanomaterial based on rGO negative charge regulation prepared according to the above method.

[0023] An electrochemical test method for the modified electrode of the AgPt bimetallic coated Ag nanomaterial based on the negative charge regulation of rGO, wherein the modified electrode is used as the working electrode, the graphite electrode is used as the counter electrode, and the saturated calomel electrode (SCE) is used as the reference electrode, and CV and DPV tests are performed, wherein the potential range of the CV and DPV tests is -0.3V-0.9V (vs. SCE; all tests are performed in a phosphoric acid or 0.1M phosphate buffer environment; before all CV and DPV test data are collected, the electrode is subjected to constant potential polarization for 15s under 0V (vs. SCE) conditions to make the electrode surface material and the phosphate doped in the film layer in a negatively charged and consistent state.

[0024] An application of the above-mentioned AgPt bimetallic coated Ag nanomaterial based on rGO negative charge regulation in electrochemical detection of gallic acid.

[0025] The beneficial effects of the present invention are:

[0026] The present invention proposes a platinum-silver bimetallic coated Ag nanocatalyst (rGO / Ag@AgPt) loaded on the surface of reduced graphene oxide (rGO) by regulating the electronic structure of the graphene carrier through negative charge. The catalyst has excellent catalytic performance for gallic acid, high sensitivity, and a wide linear range, and is suitable for the electrochemical detection of gallic acid.

[0027] The AgPt bimetallic coated Ag nanomaterial based on rGO negative charge regulation of the present invention effectively solves the interference problem in the gallic acid test process under complex environment.

[0028] The design and synthesis method of the AgPt bimetallic coated Ag nanomaterial based on rGO negative charge regulation of the present invention can provide a new idea and method for effectively solving the poisoning and activity degradation of platinum metal catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 Surface morphology of the composite material. (a) is the surface morphology of the rGO / Ag composite material; (b) is the surface morphology of the rGO / Ag@Ag9Pt1 composite material.

[0031] Figure 2 Mapping data diagram (ad) and EDS linear scan diagram (e) of rGO / Ag@Ag9Pt1 composite material.

[0032] Figure 3 CV test diagram of rGO-loaded series composite material modified electrodes in a solution containing 500 μM GA (pH 4.5) at a scan rate of 50 mV / s.

[0033] Figure 4 DPV test diagram of a series of composite materials modified electrodes loaded with rGO in a solution containing 500 μM GA (pH 4.5).

[0034] Figure 5 This is one of the electrochemical test graphs of the rGO / Ag@Ag9Pt1 composite modified electrode. Among them, (a) is the CV test graph of the rGO / Ag@Ag9Pt1 composite modified electrode in solutions with different pH values ​​containing 500μM GA at a scanning rate of 50mV / s; (b) is the DPV test graph of the rGO / Ag@Ag9Pt1 composite modified electrode in solutions with different pH values ​​containing 500μM GA.

[0035] Figure 6 This is the second electrochemical test diagram of the rGO / Ag@Ag9Pt1 composite material modified electrode, where (a) is the CV test diagram of the rGO / Ag@Ag9Pt1 composite material modified electrode at different scanning speeds in a solution containing 500μM GA (pH 4.5); (b) is the relationship between the peak current and the scanning speed of the CV test curve of the rGO / Ag@Ag9Pt1 composite material modified electrode in a solution containing 500μM GA (pH 4.5).

[0036] Figure 7 DPV test diagram of rGO / Ag@Ag9Pt1 composite modified electrode in solutions containing different GA concentrations (pH 4.5).

[0037] Figure 8 This is the standard curve of DPV test of GA (pH 4.5) on rGO / Ag@Ag9Pt1 modified electrode. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0039] Example 1 Preparation of rGO / Ag@AgPt Nanocatalyst

[0040] 1.6 ml of 47.9 mmol / L silver acetate solution was added to 25 ml of 2 mg / ml graphene oxide aqueous solution, followed by 5 mL of distilled water, 120 ml of ethylene glycol, 18 ml of methyl pyrrolidone, and 720 mg of trisodium citrate. After stirring evenly, the mixture was transferred to a hydrothermal reactor, heated to 120 ° C, and reacted for 3 hours. After cooling, the mixture was centrifuged at high speed, washed with a mixture of water and ethanol (1:1), and centrifuged again. After repeated washing and centrifugation for 3 times, the mixture was dispersed in an ethanol solution to obtain a reduced graphene oxide-supported silver nanoparticle (rGO / Ag) catalyst.

[0041] 8.2 mmol / L potassium chloroplatinate was added to the rGO / Ag ethanol dispersion according to the Ag:Pt molecular molar ratio of 10:1, 8:1, and 6:1, respectively. After stirring for 8 hours, the dispersion was centrifuged at high speed, washed with a mixture of water and ethanol (1:1) and centrifuged again. The unreacted platinum and the loosely loaded platinum metal and platinum-silver metal were washed and centrifuged and discarded. After repeated washing and centrifugation for 3 times, the dispersion was dispersed in an ethanol solution to obtain reduced graphene oxide-supported platinum-silver metal-coated silver nanoparticles (rGO / Ag@AgPt) catalysts, which were recorded as rGO / Ag@Ag according to the ratio of the coated platinum-silver metals. 12Pt1, rGO / Ag@Ag9Pt1, rGO / Ag@Ag6Pt1.

[0042] Comparative Example 1 Preparation of rGO / Ag Nanocatalyst

[0043] 1.6 ml of 47.9 mmol / L silver acetate solution was added to 25 ml of 2 mg / ml graphene oxide aqueous solution, followed by 5 mL of distilled water, 120 ml of ethylene glycol, 18 ml of methyl pyrrolidone, and 720 mg of trisodium citrate. After stirring evenly, the mixture was transferred to a hydrothermal reactor, heated to 120 ° C, and reacted for 3 hours. After cooling, the mixture was centrifuged at high speed, washed with a mixture of water and ethanol (1:1), and centrifuged again. After repeated washing and centrifugation for 3 times, the mixture was dispersed in an ethanol solution to obtain a reduced graphene oxide-supported silver nanoparticle (rGO / Ag) catalyst.

[0044] Comparative Example 2 Preparation of rGO / Pt Nanocatalyst

[0045] 1.55 ml of 8.2 mmol / L potassium chloroplatinate was added to 25 ml of 2 mg / ml graphene oxide aqueous solution, and 5 ml of 2 mM ascorbic acid solution was added. The mixture was stirred for 24 hours and then centrifuged at high speed. The mixture was washed with a mixture of water and ethanol (1:1) and centrifuged again. The mixture was washed and centrifuged three times and then dispersed in an ethanol solution to obtain a reduced graphene oxide-supported platinum nanoparticle (rGO / Pt) catalyst.

[0046] Characterization Test

[0047] Figure 1 (a) is the surface morphology of rGO / Ag composite material; Figure 1 (b) is the surface morphology of the rGO / Ag@Ag9Pt1 composite material. As can be seen from the figure, the Ag particles loaded in the rGO / Ag composite material are round particles with a particle size of 30-50nm, and the particle surface is relatively smooth. After the composite Pt, Pt reacts with the Ag in rGO / Ag through a replacement reaction, so that some sites on the Ag surface are occupied by Pt, forming an AgPt bimetal and wrapping the surface of the Ag particles. Figure 1 As shown in (b), in rGO / Ag@Ag9Pt1, the surface of the Ag particles becomes rougher after being coated with the AgPt bimetal, and the surface coating layer is composed of numerous particles with smaller particle sizes.

[0048] Figure 2 The following is the mapping data and EDS linear scan of the rGO / Ag@Ag9Pt1 composite material. As can be seen from the figure, rGO / Ag@Ag9Pt1 is a round particle with a particle size of 40-50nm, with an Ag particle in the center and a AgPt bimetallic coating on the surface. The EDS linear scan test results show that the bimetallic Ag:Pt on the surface of the Ag particle is 9:1.

[0049] Application Examples

[0050] Preparation of modified electrodes

[0051] A glassy carbon electrode with a diameter of 5 mm was polished on a polishing pad with alumina slurries with particle sizes of 3, 1, 0.3 and 0.05 μm, rinsed with distilled water, ultrasonically cleaned in anhydrous ethanol and distilled water, and dried for use. 2 mg of nanocatalyst powder and 10 μl of 5% Nafion ethanol solution were dispersed in 0.5 ml of ethanol and ultrasonicated for 30 min to form a uniform mixed suspension.

[0052] 13 μl of the mixed suspension was dropped onto the cleaned surface of the glassy carbon electrode, and after drying at room temperature, 13 μl of the mixed suspension was dropped onto the surface of the glassy carbon electrode again, and after drying at room temperature, the electrode was immersed in a solution containing 5 mM sodium hypochlorite and 10% phosphoric acid for 24 hours to reduce the graphene oxide to reduced graphene oxide, and to fully dope the graphene carrier and the Nafion membrane layer with phosphoric acid molecules.

[0053] In order to obtain a stable and reproducible electrochemical detection signal, the prepared catalyst modified electrode must be pretreated, that is, in a 5% phosphoric acid solution, a cyclic voltammetry (CV) scan is performed for 0.5 h in the potential range of -0.3V–0.9V (vs. SCE). In order to prevent the oxidation of the surface active sites of the loaded Ag metal and the desorption of phosphoric acid molecules from the catalyst support and electrode film during storage, the pretreated modified electrode needs to be immersed in a solution containing 5mM sodium hypochlorite and 10% phosphoric acid for use.

[0054] Electrochemical test methods of modified electrodes

[0055] The electrochemical experiment adopts a three-electrode system, in which the catalyst-modified electrode is used as the working electrode, the graphite electrode is used as the counter electrode, and the saturated calomel electrode (SCE) is used as the reference electrode for cyclic voltammetry (CV) and pulse voltammetry (DPV) tests. The potential range of CV and DPV tests is -0.3V-0.9V (vs. SCE). All test experiments are carried out in phosphoric acid or 0.1M phosphate buffer environment. Before collecting data for all CV and DPV tests, the electrodes are subjected to constant potential polarization for 15s under 0V (vs. SCE) conditions to make the electrode surface material and the phosphate doped in the film layer in a negatively charged and consistent state. The reduced graphene oxide carrier of the catalyst can electronically regulate the surface doped phosphate by applying an external potential, thereby optimizing the electron transfer performance of the loaded platinum-silver catalyst, so that the catalytic performance and stability of the composite catalyst reach a more optimized state. The electrode after the test needs to be immersed in a solution containing 5mM sodium hypochlorite and 10% phosphoric acid to make it stable for a long time.

[0056] The nanocatalyst powders were prepared by using the nanocatalyst powders prepared in Example 1 and Comparative Examples 1-2, respectively, to prepare modified electrodes, and then electrochemical tests were performed. The experimental results are as follows:

[0057] Figure 3 The CV test diagram of the series of composite modified electrodes loaded with rGO in a solution containing 500μM GA (pH4.5) at a scanning speed of 50mV / s. As can be seen from the figure, GA has two pairs of redox peaks on the series of composite electrodes, which is a two-electron reaction; among them, the oxidation peak of the first pair of electron redox reaction is more obvious, and its peak potential is 0.35-0.37V. The peak potential difference of the two pairs of redox peaks of GA on the series of composite electrodes is greater than 200mV, showing obvious irreversibility. In the figure, the electrocatalytic oxidation of GA on the series of composite electrodes shows obvious differences. Among them, the electrochemical response of GA on the rGO / Pt composite electrode is weak, which can be partly attributed to the fact that although Pt metal has good catalytic performance, it is prone to catalyst poisoning or catalyst deactivation in a complex environment, which significantly reduces the catalytic performance. The electrochemical response of GA on the rGO / Ag composite electrode was significantly enhanced; after composite Pt, the electrochemical response of the composite electrode to GA showed different degrees of enhancement, among which the electrochemical response of GA on rGO / Ag@Ag9Pt1 was significantly greater than that of the bimetallic coated composite materials with Ag:Pt=12:1 and 6:1, that is, rGO / Ag@Ag9Pt1 showed obvious advantages and a better metal material ratio in the catalytic oxidation of GA.

[0058] Figure 4 This is the DPV test diagram of a series of composite modified electrodes loaded with rGO in a solution containing 500μM GA (pH 4.5). It can be seen from the figure that the oxidation peak potential of GA on the series of composite modified electrodes is located at 0.30-0.32V, among which the oxidation peak potential of GA on rGO / Ag shows a slight negative shift, while on rGO / Pt there is a relatively obvious positive shift. In terms of catalytic activity, the Ag nanomaterials coated with AgPt bimetallic loaded with rGO show obvious advantages, among which the electrochemical response of rGO / Ag@Ag9Pt1 to GA catalytic oxidation is much greater than that of rGO / Ag and rGO / Pt. In terms of the selection of the Ag:Pt ratio of the coated AgPt bimetallic, rGO / Ag@Ag9Pt1 is significantly better than other Ag:Pt ratios, and this conclusion is consistent with Figure 3 Consistent.

[0059] Figure 5(a) is the CV test diagram of the rGO / Ag@Ag9Pt1 composite modified electrode in solutions with different pH values ​​containing 500μM GA at a scan rate of 50mV / s; (b) is the DPV test diagram of the rGO / Ag@Ag9Pt1 composite modified electrode in solutions with different pH values ​​containing 500μM GA. It can be seen from the figure that the pH value of the test solution has a great influence on the electrochemical response of the substance to be tested. With the increase of pH value, the corresponding oxidation peak potential of GA on the electrode shifts significantly negatively, indicating that protons participate in the reaction of the electrode process. When the pH value of the test solution increases from 4.5 to 7.0, it can be observed that the oxidation peak current of GA decreases significantly; when the pH value is greater than 7.0, no obvious oxidation peak current is observed. Therefore, the electrochemical oxidation test of GA is suitable for acidic test conditions. However, when the system test pH value is less than 4, the oxidation peak signal of GA overlaps with the interfering substances such as uric acid and dopamine, which makes the anti-interference performance of the system worse. Therefore, pH 4.5 is selected as the optimal test pH condition for GA in this system. In order to increase the sensitivity and anti-interference performance of the system, the system uses phosphoric acid doping to make the electrode surface modified film layer carry a large number of dihydrogen phosphate ions that can dissociate and accept protons, and at the same time, through external potential regulation, the electrode film layer carries a large amount of negative charge. This method can effectively regulate the concentration of negative charge on the electrode surface, so that GA has enough protons that can participate in the reaction during the electrochemical oxidation process, so that the test system can obtain higher sensitivity while less interference from substances in the solution. In addition, the XPS test results show that negative charge doping can effectively change the electronic state of the graphene carrier, further affecting the electronic distribution of the loaded platinum silver metal surface, thereby enhancing the electrochemical catalytic oxidation of the test substance GA.

[0060] Figure 6 (a) is the CV test graph of the rGO / Ag@Ag9Pt1 composite modified electrode at different scanning speeds in a solution containing 500μM GA (pH 4.5); (b) is the peak current and scanning speed relationship graph of the CV test curve of the rGO / Ag@Ag9Pt1 composite modified electrode in a solution containing 500μM GA (pH 4.5). It can be seen from the figure that the electrochemical curve of GA on the rGO / Ag@Ag9Pt1 composite modified electrode shows two pairs of redox peaks, among which the first pair of redox peak signals is more obvious, and as the scanning speed increases, the oxidation peak current of GA increases. From the relationship curve of the peak current of the first pair of redox peaks of GA and the scanning speed, it can be seen that the oxidation peak current and reduction peak current of GA are proportional to the first power of the scanning speed, and the linear regression equation of its oxidation peak current and scanning speed is y=3.1976x+8.6405, R 2 =0.9996, the linear regression equation of reduction peak current and scanning speed is y=-3.1014x-1.1716, R2 =0.9988, indicating that the electrochemical redox reaction of GA on the rGO / Ag@Ag9Pt1 composite modified electrode is a diffusion-controlled process.

[0061] Figure 7 The DPV test diagram of the rGO / Ag@Ag9Pt1 composite modified electrode in solutions containing different GA concentrations (pH 4.5). It can be seen from the figure that the oxidation current potential range of different concentrations of GA on the modified electrode is 0.15V-0.42V, and the oxidation peak potential is around 0.30V; as the GA concentration increases, the electrochemical response signal of GA on the modified electrode also increases, and the detection limit is 0.005μM. In order to test the effect of interference on the test of GA on the rGO / Ag@Ag9Pt1 composite modified electrode, 10mM K + 、Na + 、Zn 2+ , Cl - GA samples with different concentrations mixed with 1 mM glucose and 0.5 mM uric acid were prepared for DPV testing. The results showed that these metal cations, anions and organic compounds had no significant effect on the determination of GA, indicating that the rGO / Ag@Ag9Pt1 composite material modified electrode has good selectivity and anti-interference for the test of GA.

[0062] Figure 8 The standard curve of DPV test of GA (pH 4.5) on rGO / Ag@Ag9Pt1 modified electrode. It can be seen from the figure that in the concentration range of 0.005μM-500μM detected by the present invention, there is a bilinear relationship between GA concentration and peak current. At high concentration (100μM-500μM), the linear curve is y=0.11276x+19.721, and its correlation coefficient R 2 =0.98737. At low concentrations (0.005 μM-100 μM), the linear curve is y=0.2871x+1.3069, and its correlation coefficient R 2 =0.98658.

[0063] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A AgPt bimetallic coated Ag nanomaterial based on rGO negative charge regulation, characterized in that: The preparation method comprises: adding a silver acetate solution to a graphene oxide aqueous solution, adding distilled water, ethylene glycol, methyl pyrrolidone and trisodium citrate in sequence, stirring evenly and then performing a hydrothermal reaction; cooling and then centrifuging, washing with a water and ethanol mixture and then centrifuging again, and repeatedly washing and centrifuging for multiple times to obtain a silver nanocatalyst rGO / Ag loaded with reduced graphene oxide; dispersing rGO / Ag in an ethanol solution, adding potassium chloroplatinate, stirring and then centrifuging, washing with a water and ethanol mixture and then centrifuging again, and repeatedly washing and centrifuging for multiple times to obtain a platinum and silver metal-coated silver nanocatalyst rGO / Ag@AgPt loaded with reduced graphene oxide; wherein the molar ratio of Ag:Pt is 10:1-6:1, respectively.

2. The AgPt bimetallic coated Ag nanomaterial based on rGO negative charge regulation according to claim 1, characterized in that: The particle size of the rGO / Ag@AgPt is 40-50nm.

3. A method for preparing Ag nanomaterials coated with AgPt bimetallic materials based on rGO negative charge regulation according to claim 1 or 2, characterized in that: The following steps are involved: S1, adding silver acetate solution to graphene oxide aqueous solution, and then adding distilled water, ethylene glycol, methyl pyrrolidone, and trisodium citrate in sequence, stirring evenly and then performing hydrothermal reaction; cooling and centrifuging, washing with a mixture of water and ethanol and then centrifuging again, and repeatedly washing and centrifuging multiple times to obtain a silver nanocatalyst rGO / Ag supported on reduced graphene oxide; S2, dispersing rGO / Ag in an ethanol solution, adding potassium chloroplatinate, stirring the reaction and then centrifuging, washing with a mixture of water and ethanol and then centrifuging again, after repeated washing and centrifugation, obtaining a platinum-silver metal-coated silver nanocatalyst rGO / Ag@AgPt supported by reduced graphene oxide.

4. The preparation method according to claim 3, characterized in that: The concentration of the silver acetate solution is 45-50 mmol / L; the graphene oxide aqueous solution is 1.8-2.2 mg / mL; and the potassium chloroplatinate is 8.0-8.4 mmol / L.

5. The preparation method according to claim 3, characterized in that: The ratio of the silver acetate solution, the graphene oxide aqueous solution, the distilled water, the ethylene glycol, the methyl pyrrolidone and the trisodium citrate is 1.5-1.8 mL: 22-28 mL: 4-6 mL: 110-130 mL: 16-20 mL: 700-730 mg.

6. The preparation method according to claim 3, characterized in that: In step S1, the temperature of the hydrothermal reaction is 110-130°C and the time is 2.5-3.5 hours; in step S2, the stirring reaction time is 7-9 hours.

7. A method for preparing a modified electrode of AgPt bimetallic coated Ag nanomaterial based on rGO negative charge regulation according to claim 1 or 2, characterized in that: The following steps are involved: (1) A glassy carbon electrode with a diameter of 5 mm was polished on a polishing pad with alumina slurries with particle sizes of 3, 1, 0.3 and 0.05 μm, respectively, rinsed with distilled water, ultrasonically cleaned in anhydrous ethanol and distilled water, and then dried for use; 2 mg of reduced graphene oxide-supported platinum-silver metal-coated silver nanocatalyst rGO / Ag@AgPt powder and 10 μl of 5% Nafion ethanol solution were dispersed in 0.5 ml of ethanol and ultrasonicated for 30 min to form a uniform mixed suspension; (2) 13 μl of the mixed suspension was added dropwise onto the surface of the cleaned glassy carbon electrode, and after drying at room temperature, 13 μl of the mixed suspension was added dropwise onto the surface of the glassy carbon electrode again, and after drying at room temperature, the electrode was immersed in a solution containing 5 mM sodium hypochlorite and 10% phosphoric acid for 24 h to reduce the graphene oxide to reduced graphene oxide, and to fully dope the graphene carrier and the Nafion membrane layer with phosphoric acid molecules; (3) The prepared modified electrode was pretreated by performing cyclic voltammetry (CV) scanning for 0.5 h in a 5% phosphoric acid solution at a potential range of -0.3 V–0.9 V (vs. SCE); the pretreated modified electrode was immersed in a solution containing 5 mM sodium hypochlorite and 10% phosphoric acid for standby use.

8. A modified electrode of Ag nanomaterials coated with AgPt bimetallic material based on rGO negative charge regulation prepared according to the method of claim 7.

9. An electrochemical testing method for the modified electrode of AgPt bimetallic coated Ag nanomaterial based on rGO negative charge regulation according to claim 8, characterized in that: The modified electrode was used as the working electrode, the graphite electrode was used as the counter electrode, and the saturated calomel electrode (SCE) was used as the reference electrode to perform CV and DPV tests. The potential range of the CV and DPV tests was -0.3V-0.9V (vs. SCE; all tests were performed in a phosphoric acid or 0.1M phosphate buffer environment; before collecting data for all CV and DPV tests, the electrodes were subjected to constant potential polarization at 0V (vs. SCE) for 15s to make the electrode surface material and the phosphate doped in the film layer in a negatively charged and consistent state.

10. Use of the AgPt bimetallic coated Ag nanomaterial based on rGO negative charge regulation as claimed in claim 1 or 2 in electrochemical detection of gallic acid.

Citation Information

Cited By

  • Graphene-based polyaniline supported AgAu bimetallic composite catalyst and preparation and application thereof

    CN121869459A